Arterial Stiffness as a Predictor of Clinical Hypertension. Issue 8 (27th April 2015) - Zheng, Xiaoming; Jin, Cheng; Liu, Yeqiang; Zhang, Jing; Zhu, Ying; Kan, Shuting; Wu, Yuntao; Ruan, Chunyu; Lin, Liming; Yang, Xinchun; Zhao, Xingquan; Wu, Shouling
<x xml:space="preserve">Abstract</x> The association between vascular stiffening and blood pressure is likely bidirectional. The present study was designed to examine temporal relationships among vascular stiffness, blood pressure progression, and hypertension. The Asymptomatic Polyvascular Abnormalities Community study is a community‐based, prospective, long‐term follow‐up observational study. The present investigation is based on the baseline examinations (2010–2011) and the first follow‐up measurements (2012–2013) included in the study. A total of 4025 participants were followed for an average of 27 months. Of 2153 participants free of hypertension at the baseline examination, 432 (20.07%) had incident hypertension. The authors observed that brachial‐ankle pulse wave velocity (baPWV) was an independent predictor of incident hypertension. baPWV during baseline examination was positively associated with higher systolic blood pressure, diastolic blood pressure, pulse pressure, and mean arterial pressure during the first follow‐up examination. baPWV but not blood pressure during baseline examination was associated with baPWV during the first follow‐up examination. This study not only provides evidence that baPWV is an independent predictor of blood pressure progression and incident hypertension, but also provides evidence that blood pressure is not associated with baPWV after adjusting for baseline baPWV.